Inclusive Learning System in Arabic Subjects for Mentally Retarded Students - Putri Tsaltsa Nabilla; Nurul Latifatul Inayati (Yayasan Letiges Konsultan Sosial, 2024)
This study aims to determine the application of an inclusive learning system in Arabic language subjects for mentally retarded students. This research is a qualitative study with a descriptive qualitative approach. This type of research is field research in which the data collection process is carried out directly in the field with case study techniques for mentally retarded children in Arabic classes at Al Firdaus Junior High School, especially in class IX. Data collection was done through interviews, observations and document studies. The data were analyzed using interactive data analysis techniques: data collection, data reduction, data presentation and conclusion drawing. The results show that inclusive learning is implemented using a modification system that includes content, process, evaluation, product, time and learning environment modification. This means that the subject matter, learning process, type of evaluation, products to be produced, learning time and learning environment will be adjusted to the conditions and needs of students to help them gain comfort in learning, which will help them achieve the desired competencies. The obstacles encountered are related to moods that are sometimes not good, as well as difficulties in writing Arabic writing, reading, interpreting and memorizing.